Bundle for prevention of urinary tract infection in Adult ICU: a literature review (Research, Society and Development, 2022)
There are several infections related to health care (HAI) associated with different procedures, however, Urinary Tract Infections (UTI) draw attention because they are one of the most prevalent, despite the great preventive potential at the time of catheterization. In order to improve care and the care process, the concept of bundle emerges, inserted in good practices, which would be small well-evidenced intervention “packages” in order to ensure patient safety. The aim of this study was to review articles on the UTI prevention bundle of patients in intensive care. This is an integrative review using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) technique of research articles. We reviewed 20 articles that fit the criteria for research refinement, published between 1996 and 2016, with a predominance of 85% of production coming from the Southeast region. The main UTI preventive recommendations found were: hand washing before the procedure; maintenance of the closed system and the collection bag below the bladder; catheter insertion using aseptic technique and cleaning of the urethral meatus. It is then concluded that there is a reduced production of articles by the nursing team and inexpressive/nonexistent in other regions of the country.